RETROGRADE INTRARENAL SURGERY AS A METHOD OF IMPROVING THE ENDOSCOPIC MANAGEMENT OF OCCLUSIVE CONCREMENTS OF THE UPPER PARTS OF THE URETER - Ivashchenko, D.M.; Dudchenko, M.O.; Kravtsiv, M.I.; Shevchuk, M.P.; Ivanova, H.O. (World of Medicine and Biology, 2023)
The paper presents upper ureter stone treatment with use of retrograde intrarenal surgery. This is the latest method, which has advantages in treatment of complex cases of nephrolithiasis, stone translocations and residual cases. We analyzed treatment of patients with ureteral stones. Two representative groups were formed and underwent surgical interventions. Patients of first group underwent contact lithotripsy with semi-rigid ureteroscope, in patients of group 2 used flexible ureteroscope. We compare total operation time, average size and density of stones, presence of residual fragments, surgical and postoperative complications. Performing lithotripsy using a retrograde intrarenal surgery provides higher frequency of achieving “stone-free state”, which is the ultimate goal of intervention. Also, this is a method that has fewer intraoperative complications, but has a slightly longer duration of surgical intervention. The use of combination of retrograde intrarenal surgery and semi-flexible ureteroscopy should facilitate operations, speed up patient recovery and minimize complications.